Desenvolvimento e perfil sensorial de hamburguer vegetal adicionado de resíduos de coco babaçu - Amaral, Vitor Soares do (2025)
Combining technology with the traditional knowledge of agroextractivist communities and babassu coconut “breakers woman”, a plant-based analog burger technology was developed using residues from the fruit and other ingredients such as rice, bean flour, and lentils, in addition to typical seasonings and spices used in animal-based burgers. The work carried out encourages and values the ancestral knowledge about babassu coconut breaking, focusing on the Sustainable Development Goals (SDGs): 2 (Zero Hunger and Sustainable Agriculture), 10 (Reduced Inequalities), 11 (Sustainable Cities and Communities), 12 (Responsible Consumption) and 17 (Partnerships for the Goals). Four formulations were developed with varying levels of babassu coconut residue and coconut oil: 15% babassu coconut residue and 25% coconut oil (15F25G), 20% babassu coconut residue and 20% coconut oil (20F20G), 30% babassu coconut residue and 10% coconut oil (30F10G), and 35% babassu coconut residue and 5% coconut oil (35F5G). The sensory profile of the samples was outlined through focus groups using the methods Check-All-That-Apply (CATA), Rate-All-That-Apply (RATA), and hedonic analysis. The samples were classified as having a uniform and pleasant color. Other highlighted attributes included aroma and texture. The aroma indicated that babassu coconut residue did not compromise the perception of the product's smell, receiving an average score of 3.1 on a scale of 1 to 5. The texture of the samples was well-received, with averages ranging from "liked a little" to "liked a lot." No notable differences were observed between the samples, demonstrating that the added babassu coconut residue maintained the sensory characteristics of the texture. All four samples received positive evaluations, with the overall average described by the hedonic term "liked a lot." The flavor ranged from "liked a little" to "liked a lot" (7.2 ± 0.8), with the 35F5G formulation being the most accepted, reflecting the preference for higher or more balanced concentrations of babassu coconut residue. Finally, the purchase intent was highest for the 15F25G and 35F5G formulations, with 70% and 80% percentages, respectively. Therefore, the study indicated that higher concentrations of babassu coconut residues or more excellent balance may attract more consumers. These results suggest that babassu coconut residue has enormous potential as a sustainable and functional ingredient for the plant-based food sector. The technological innovation presented goes hand in hand with respect for cultural tradition, promoting environmental sustainability and social inclusion of the communities involved. Furthermore, the results highlight that the developed burgers align with more responsible economic and dietary practices, strengthening the market for safe and healthy foods and contributing to achieving the Sustainable Development Goals.